2021
DOI: 10.33009/fsop_jpss124641
|View full text |Cite
|
Sign up to set email alerts
|

Coming to College Hungry

Abstract: This exploratory descriptive, single-university study (N=700) joined institutional, external, and survey data to examine first-year students’ food insecurity links to non-cognitive attributes and first-semester performance and persistence. Regressions indicate LGBTQ, multi-racial, international, transfer, and first-generation students exhibit increased food insecurity. Food insecurity linked with psychological distress, financial stress, amotivation, and intent to engage with peers but not to faculty, staff, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…These findings provide insights into several ways that both on-campus and off-campus food-security programs could be more inclusive of LGBTQIA+ students. Primarily, universities need gender and sexuality resource centers, like the UNT Pride Alliance, that invest in the success of LGBTQIA+ students by providing resources for the specific and unique needs of LGBTQIA+ students (Collier et al, 2021). These centers can play a pivotal role in providing the infrastructure necessary for the forthcoming recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings provide insights into several ways that both on-campus and off-campus food-security programs could be more inclusive of LGBTQIA+ students. Primarily, universities need gender and sexuality resource centers, like the UNT Pride Alliance, that invest in the success of LGBTQIA+ students by providing resources for the specific and unique needs of LGBTQIA+ students (Collier et al, 2021). These centers can play a pivotal role in providing the infrastructure necessary for the forthcoming recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…According to The Hope Center, 65% of students who identify as LGBTQIA+ experience some form of basic needs insecurity (food or housing) (The Hope Center, 2021a). Collier et al (2021) found a relationship between students who selfidentified as LGBTQIA+ and food insecurity. Additional research found that transgender and genderqueer students had a higher risk of food insecurity than cis-gender students (Diamond et al, 2020;Hasket et al, 2020;Keefe et al, 2020;Laska et al, 2021;Riddle et al, 2020).…”
Section: Introduction and Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…The Hope Center found that students who identify as LGBTQ were more likely to experience basic needs insecurity and reported that 65% of LGBTQ students experience some form of basic needs insecurity, such as food insecurity, housing insecurity, and/or homelessness (The Hope Center, 2021). There has, however, been a lack of in-depth research on food insecurity amongst LGBTQIA2S+ university students, although recent research has begun to explore this topic (Collier et al, 2021;Henry et al, 2023). A myriad of factors may contribute to this gap in research, such as research on specific population intersections being more complex to study and analyze in comparison to studies focused on single population factor or a lack of research funding.…”
Section: Introductionmentioning
confidence: 99%